THE IMPACT OF DIETARY ORGANIC FOOD ON THE HAEMATOLOGICAL PARAMETERS, BODY COMPOSITION AND GROWTH OF SILVER CARP RAISED IN RECIRCULATING AQUACULTURE SYSTEM (Journal of Medical & Health Sciences Review, 2025)
The effects of different dietary doses of organic selenium (Se) on the growth, body composition, and haematological parameters of silver carp were evaluated in a feeding experiment. The basal diet was supplemented with selenium at levels of 0.0, 0.5, 1, and 2 mgkg⁻¹. A total of 25 fish were randomly stocked into 500 L tanks using Recirculating Aquaculture System (RAS) technology and fed for ten weeks. Fish fed diets containing 0.5 mgkg⁻¹, 1 mgkg⁻¹, and 2 mgkg⁻¹ Se showed significantly higher weight gain, final body weight, and specific growth rate (p0.05). Whole-body composition analysis revealed that fish fed 1 mgkg⁻¹ Se had significantly higher body moisture and protein levels on a dry weight basis (p